Coupling of Voltage-Sensors to the Channel Pore: A Comparative View - Vardanyan, Vitya; Pongs, Olaf (Frontiers in Pharmacology, 2012)
The activation of voltage-dependent ion channels is initiated by potential-induced conformational rearrangements in the voltage-sensor domains that propagates to the pore domain and finally opens the ion conduction pathway. In potassium channels voltage-sensors are covalently linked to the pore via S4-S5 linkers at the cytoplasmic site of the pore domain. Transformation of membrane electric energy into the mechanical work required for the opening or closing of the channel pore is achieved through an electromechanical coupling mechanism, which involves local interaction between residues in S4-S5 linker and pore-forming alpha helices. In this review we discuss present knowledge and open questions related to the electromechanical coupling mechanism in most intensively studied voltage-gated Shaker potassium channel and compare structure-functional aspects of coupling with those observed in distantly-related ion channels. We focus particularly on the role of electromechanical coupling in modulation of the constitutive conductance of ion channels.